Los contenidos e interpretaciones de los sueños en el mundo shuar. - Clemente, Entza (2003)
Introduction. Referential framework: motivation research. Theoretical Framework: Psychoanalytic theories of dreams. Sleep disorder. Marco empírito. Theory Shuar dream world. What is the dream from the worldview of the Shuar world. Mythological aspects of sleep. The ethnography of dream and vision. Dream and vision. Types of visions. The types of dreams. Why dreams change our lives. What is the Jivaro religion. Sacred rules by ingesting psychotropic substances. Theory of the soul and spirit. Outline of Shuar dream interpretation. Methodological aspects. Conclusion. Recommendation. Bibliography. attachments